Social representation of social expert reports in court judgements. A relevant analysis to forensic social work - Ferri-Fuentevilla, Elena; Navarro-Ardoy, Luis; Muñoz Moreno, Rocío (Cuadernos de Trabajo Social, 2024)
This article presents a novel contribution in the judicial field through the analysis of the social representation of expert reports in judgments handed down in Spain from 2000 to 2019. Social expert opinions are presented as evidence in judicial proceedings to assist judges in their decision-making, and despite their distinction and contribution, they currently represent an underexplored field. The purpose of this article is relevant in that it allows evidence to be generated through the analysis of the themes or issues that appear in judgments together with the content used by judges to uphold or reject claims. The strategy for this analysis is based on lexicometry using Iramuteq software, which allows us to deepen and categorise the lexical worlds, the type of relationships established between terms, as well as the contextual-relational dimension of the conditions of production of the judges' discourse around the social expert report.